Seasonal variability of sea surface pCO2 and air-sea CO2 flux in a high turbidity coastal ocean in the vicinity of the East China Sea - Yang, Zhedong; Yang, Xufeng; Zhang, Cai; Jin, Yimin; Hu, Xupeng; Zhou, Xian; Zhuang, Tonghui; Ning, Jianghao; Zeng, Jiangning; Yu, Peisong (Frontiers in Marine Science, 2025)
The sea surface partial pressure of CO2 (pCO2) and air-sea carbon flux in estuarine and bay areas, influenced by both natural and anthropogenic factors, remain poorly understood and inadequately assessed. This study, based on seasonal underway observations conducted in 2024, analyzed the seasonal variations in surface seawater pCO2 and air-sea CO2 flux in the high-turbidity coastal waters of Zhejiang, including Hangzhou Bay (HZB), Xiangshan Bay (XSB), Sanmen Bay (SMB), and the nearshore waters (NSW). The results indicate that the pCO2 in the study area ranged from 194 to 739 μatm throughout the year, exhibiting significant spatiotemporal heterogeneity. In HZB, the lowest pCO2 was observed in winter, averaging 453 μatm, whereas the values in spring and summer were around 600 μatm, with a subsequent decline to 481 μatm in autumn. In XSB, pCO2 reached its minimum in winter (194 μatm), attributed to vigorous biological activity, and peaked in spring, averaging 639 μatm. In SMB, pCO2 was relatively lower in autumn and winter ( 470 μatm), and higher in spring and summer ( 640 μatm). In the NSW, pCO2 was lower in winter and spring ( 445 μatm), and increased to 510 μatm in summer and autumn. The pCO2 was predominantly regulated by sea surface temperature and horizontal mixing, while other factors like biological activity also had significant impacts. The annual average CO2 flux was 6.0±3.7 mmol m-2 d-1 in HZB, 1.2±2.3 mmol m-2 d-1 in XSB, 7.0±3.2 mmol m-2 d-1 in SMB and 5.2±5.9 mmol m-2 d-1 in the NSW. Higher wind speeds in autumn and winter, coupled with elevated the pCO2 difference between the surface water and the atmosphere (ΔpCO2) in spring and summer, collectively drove the seasonal variations in CO2 flux. On an annual scale, both the estuarine and bay areas and the nearshore regions functioned as carbon sources.